1979
DOI: 10.3181/00379727-161-40494
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Prolactin, Growth Hormone and Insulin in Genetically Diabetic (db/db) Mice

Abstract: The mutant diabetic (db/db) mouse was first described by Hummel et al. in 1966 (1). These mice suffer from metabolic disturbances resembling not insulin-dependent diabetes mellitus in man. The symptoms include hyperglycemia, polyuria, glycosuria and marked obesity. Like the obese mutant ob/ ob, the db/db mice exhibit a paradoxical hyperglycemia concomitant with hyperinsulinemia in early stages of development (2). In later life, the insulin levels of db/db mice return towards normal, but the hyperglycemia persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The stimulatory effect of estrogen on hepatic PRLR may be mediated, at least in part, by the hypothalamus-hypophyseal system, since estrogen is incapable of increasing the level of PRLR in hypophysectomized rats (Norstedt & Mode 1982) and pituitary PRL is able to up-regulate its own receptor (Manni et al 1978). In female diabetic mice, the levels of PRL in orbitally collected sera were lower than normal until 12 weeks of age, and thereafter the levels increased to normal levels (Sinha et al 1979). These results are consistent with our findings of the changes of hepatic PRLR mRNA in diabetic female mice during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effect of estrogen on hepatic PRLR may be mediated, at least in part, by the hypothalamus-hypophyseal system, since estrogen is incapable of increasing the level of PRLR in hypophysectomized rats (Norstedt & Mode 1982) and pituitary PRL is able to up-regulate its own receptor (Manni et al 1978). In female diabetic mice, the levels of PRL in orbitally collected sera were lower than normal until 12 weeks of age, and thereafter the levels increased to normal levels (Sinha et al 1979). These results are consistent with our findings of the changes of hepatic PRLR mRNA in diabetic female mice during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Coleman & Burkart (1977) have reported that plasma corticosterone levels are elevated in diabetes mice, whilst Carson, Hanker & Kirschner (1982) reported an increase in adrenal catecholamines and enzymes involved in their synthesis. Plasma prolactin, growth hormone and insulin at different times in the life span of the mutants have been reported by Sinha, Baxter, Larson & Vanderlaan (1979). Apparently db/db mice show a decreased thyroidal response to thyrotropin (Bagchi, Brown, Shivers, Lucas & Mack, 1981).…”
Section: Miscellaneous Endocrine-relatedfunctionsmentioning
confidence: 99%
“…Several studies have shown that GH levels are decreased in the STZ‐induced diabetic rat and diabetic ( db/db ) mouse (2427). Therefore, alterations in levels of GH in the STZ‐diabetic rat maydirectlyor indirectly regulate KBP expression.…”
mentioning
confidence: 99%